ANALISIS FRAMING PEMBERITAAN PROGRAM MAKAN GRATIS OLEH PRABOWO DAN GIBRAN DI MEDIA MASSA KOMPAS.COM DAN SUARA.COM 2024: ANALISIS FRAMING PEMBERITAAN PROGRAM MAKAN GRATIS OLEH PRABOWO DAN GIBRAN DI MEDIA MASSA KOMPAS.COM DAN SUARA.COM 2024 - Maghiesswara Bayu Witcaksono Jati; Athok Murtadlo S (LPPM Stikosa-AWS, 2025)
This study analyzes the free lunch initiative initiated by Prabowo Subianto and Gibran Rakabuming Raka by examining public coverage regarding the program's effectiveness and benefits. The study examined news reports from Kompas.com and Suara.com regarding the free lunch program. The program stems from the vision, mission, and work plan of candidate pair number 2, Prabowo and Gibran, which will be implemented if they are elected and confirmed as President and Vice President of the Republic of Indonesia for the 2025–2029 period. The study used qualitative descriptive analysis methods to explore the program's impact on social welfare, how Kompas.com and Suara.com packaged news about the free lunch policy by candidate pair number 2, and the communication policies and programs presented to the public during the program's implementation. This study also examined how the mass media packaged and broadcast news related to the program to their audiences. The study revealed that Kompas.com and Suara.com adopted different framing approaches in covering the free lunch program. Kompas.com tends to employ a more in-depth and balanced framing, both when covering public debates and when discussing the political implications of the program at cabinet meetings. This allows readers to critically understand issues from multiple perspectives. Suara.com, on the other hand, focuses more on social media dynamics and a single narrative, which is effective in drawing attention to viral issues but lacks comprehensive policy analysis. Nevertheless, both media outlets maintain a neutral role by reporting on various perspectives without taking sides.